Obtención de curvas galvanostáticas y ensayos de resistencia a la polarización en varillas de construcción astm a42 en solución de agua al 3,5% de cloruro de sodio - Corte Morquecho, Daniel Estuardo (2010)
The objective of this project report is to find the speed grade of ASTM A42 steel corrosion in saline 3.5% NaCl, design an electrochemical cell polarization and building a calomel reference electrode saturated. The methodology used in this work is based on the technique of linear polarization resistance or also known as linear polarization, we will make use of the Stern-Geary equation and Faraday to determine the density and corrosion rate respectively. Also shows a photomicrograph of the steel under study. He then performed a comparative analysis of the technique with two types of specimens, the first direct contact with the solution and the second is embedded in concrete. The results reveal that the sample is not embedded in concrete has a lower polarization resistance hence the corrosion rate in itself is very fast.    Finally, it presents findings and recommendations on this job.